Influence of Swimming Program on the Blood Pressure of Pregnant Hypertensive Rats and Their Fetuses - Sene, Letícia de B. [UNESP]; Damasceno, Débora C. [UNESP]; Rocha, Renato; Iessi, Isabela L. [UNESP]; Peraçoli, José C. [UNESP]; Volpato, Gustavo T. (Springer Nature, 2021)
The hypertension incidence and its complication on pregnant women are growing and can lead to adverse consequences on their fetuses. However, it is known that regular exercise practice can be healthful to hypertensive pregnant women but harmful to fetal growth. So, the objective of this study was to evaluate the effects of exercise beginning before pregnancy or during pregnancy on the maternal blood pressure and reproductive outcome and on the fetal development of spontaneously hypertensive rats (SHR). Pregnant SHR were randomly distributed into three experimental groups: (1) SHR-Control, non-exercised; (2) SHR-Ex0, rats submitted to physical exercise (swimming program) from day zero to 20 of pregnancy; (3) and SHR-ExPr, rats submitted to swimming program before and during pregnancy. At end of pregnancy (day 21), the rats were anesthetized, and reproductive parameters and fetal development were assessed. Blood pressure was reduced at the end of pregnancy in all the groups. Regardless of swimming exposure time, there was reduced maternal weight gain. The exercise decreased fetal weight at term pregnancy, with a higher percentage of small for gestational age (SGA) fetuses and lower number ossification sites, indicating intrauterine growth restriction (IUGR). In conclusion, our findings provide insight to support that swimming exercise in pregnant SHR impairs fetal development, causing IUGR and visceral malformations. Therefore, the indication of physical exercise must be defined very carefully, as it can compromise fetal development.
Keywords: Exercise; Fetuses; Hypertension; Pregnancy; Rats